Characteristics Of Transformational Educational Leadership In The Era Of Society 5.0 The Perspective Of The Quran - Pranoto, Ahmad Hadi; Savana, Oseolla; Ulfatussyarifah, Ulfatussyarifah; Assharofi, Faiz Abdul Majid; Lutfiyah, Lutfiyah (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This article discusses the transformational characteristics of educational leadership in the era of society 5.0 from an Al-Qur'an perspective. The aim of this research is to analyze the characteristics of transformational leadership and their implications for education in the era of society 5.0 from a Koranic perspective. This research uses the library research research method. In the process of interpreting verses concerning leadership in education, the author uses the maudhui (thematic) method. Meanwhile, the results of this research are that the characteristics of transformational leadership from a Koranic perspective can be carried out through deliberation as the key to openness in an educational institution, fairness, honesty and objectivity, innovation, and working together. Meanwhile, regarding the implications of educational transformational leadership in the era of society 5.0 from the Koranic perspective, it is very influential in advancing education, namely by leaders not only having good personality traits, but leaders in the current era must also be able to develop developing technology, paying attention to the social impacts that occur. in the field, and maintaining data privacy and security as a process of creating more advanced educational institutions.